MaxEnt-Based Predictions of Suitable Potential Distribution of Leymus secalinus Under Current and Future Climate Change - Shimeng Zhao; Zongxian Zhang; Changyu Gao; Yiding Dong; Zeyao Jing; Lixia Du; Xiangyang Hou (Plants)
Grassland degradation is a serious ecological issue in the farming–pastoral ecotone of northern China. Utilizing native grasses for the restoration of degraded grasslands is an effective technological approach. Leymus secalinus is a superior indigenous grass species for grassland ecological restoration in northern China. Therefore, the excavation of potential distribution areas of L. secalinus and important ecological factors affecting its distribution is crucial for grassland conservation and restoration of degraded grasslands. Based on 357 data points collected on the natural distribution of L. secalinus, this study employs the jackknife method and Pearson correlation analysis to screen out 23 variables affecting its spatial distribution. The MaxEnt model was used herein to predict the current suitable distribution area of L. secalinus and the suitable distribution of L. secalinus under different SSP scenarios (SSP1-26, SSP2-45, and SSP5-85) for future climate. The results showed the following: (1) Mean diurnal temperature range, annual mean temperature, precipitation of the wettest quarter, and elevation are the major factors impacting the distribution of L. secalinus. (2) Under the current climatic conditions, L. secalinus is mainly distributed in the farming–pastoral ecotone of northern China; in addition, certain suitable areas also exist in parts of Xinjiang, Tibet, Sichuan, Heilongjiang, and Jilin. (3) Under future climate change scenarios, the suitable areas for L. secalinus are generally the same as at present, with slight changes in area under different scenarios, with the largest expansion of 97,222 km2 of suitable area in 2021–2040 under the SSP1-26 scenario and the largest shrinkage of potential suitable area in 2061–2080 under the SSP2-45 scenario, with 87,983 km2. Notably, the northern boundary of the middle- and high-suitability areas is reduced, while the northeastern boundary and some areas of Heilongjiang and Jilin are expanded. The results of this study revealed the suitable climatic conditions and potential distribution range of L. secalinus, which can provide a reference for the conservation, introduction, and cultivation of L. secalinus in new ecological zones, avoiding the blind introduction of inappropriate habitats, and is also crucial for sustaining the economic benefits associated with L. secalinus ecological services.